2014
DOI: 10.7314/apjcp.2014.15.20.8685
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Research on the Expression, Purification and Function of the Apoptotic Fusion Protein, Sival

Abstract: The objective of the present study was to investigate cloning, expression, and functions of the recombinant protein, Siva1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…Taken together, stable knockdown of SIVA in 231L cells significantly enhanced cell migration and invasion, effects that were reversed after re-introducing the expression of SIVA-WT. This highly suggests that SIVA is involved in the regulation of 231L cell mobility and invasiveness as previously reported in other cell lines such as breast MCF7 and colorectal HCT116 cells [21,42], and now validated in MB-MDA-231 cells.…”
Section: Plos Onesupporting
confidence: 82%
“…Taken together, stable knockdown of SIVA in 231L cells significantly enhanced cell migration and invasion, effects that were reversed after re-introducing the expression of SIVA-WT. This highly suggests that SIVA is involved in the regulation of 231L cell mobility and invasiveness as previously reported in other cell lines such as breast MCF7 and colorectal HCT116 cells [21,42], and now validated in MB-MDA-231 cells.…”
Section: Plos Onesupporting
confidence: 82%
“…Previous research found that bacterially expressed Siva 1 performed anticancer activities: suppressed the invasion, migration and induced apoptosis of colon cancer cells. 11 In addition, Siva 1 protein also found significantly inhibited the tumor metastasis of the nasopharyngeal carcinoma tumor-bearing mice. 22 Based on the former study, we hypothesized that Siva 1 may play a role in the migration and invasion of cervical cancer.…”
Section: Discussionmentioning
confidence: 92%
“…10 Whatsmore, His-Siva 1 recombinant protein was found to inhibit migration and invasion of HCT116 cells. 11 And our previous study found that Siva 1 plays a role in restricting EMT and inducing apoptosis by phosphorylation of stathmin and polymerization of α-tubulin. 12 Despite these studies, the expression of Siva 1 in cervical cancer and its biological function are still unclear.…”
Section: Introductionmentioning
confidence: 93%
“…His-Siva-1 recombinant protein inhibited invasion and migration of HCT116 cells. 19 The C-terminal domain (aa residues 84-175) expressed in bacteria as a GST-fusion protein caused apoptosis in Jurkat leukemia cells and its biophysical properties were studied. 20 The authors found monodispersion of the protein in solution with a predominant unfolded and elongated shape.…”
Section: Siva-1 Is a Proapoptotic Protein With Anticancer Activitymentioning
confidence: 99%